Темпоральная стилизация при переводе прозы (с немецого на русский) - Alekseeva, Irina (Acta Polono-Ruthenica, 2021)
When translating a literary text from a more or less remote past, a translator has to resort to some kind of imitation of the past text features, which is traditionally called archaization or temporal stylization. The fundamentals of temporal stylization were outlined in A. Fedorov’s works and later developed by a number of scholars, yet the research into archaization as a translation strategy has started only recently. The article looks into the functions of temporal stylization, such as transferring the reader into a distant epoch; increasing the effect of the fictional play; rendering the cultural dynamics through the text, reflecting the text’s various generic qualities, including the archaic ones. The illustrative examples come from the author’s own translation work: 19th century Romantic prose (T. Hoffman, L. Tieck), Austrian folk tales, private correspondence (W.A. Mozart’s letters), suggesting that the repertoire of the expressive means to render the historic colouring was found out through precedents. The author lays out her ideas about the possibility of self-evaluation in translation and puts forward the hypothesis that the type of temporal stylization depends on the type of the text. Temporal archaization is understood as a complex of typological text features and conventions, style registers and variations of the language norm. The research opens up a field for developing micro and macro strategies for literary translation.